Effects of the electron–hole pair in Auger and X-ray photoemission spectroscopy from surfaces of Fe–Si - Gervasoni, Juana Luisa (2015)
In this work, we investigate in detail the effects due to the interaction between an electron and a stationary positive ion (or atomic hole) in the neighborhood of a surface of Fe–Si, having a strong plasmon peak in their electron energy loss spectra, when it is excited with synchrotron radiation. We take into account the effects due to the sudden creation of an electron and the residual holes, one in the case of X-ray photoemission spectroscopy (XPS) and two in the case of Auger electron spectroscopy (AES). We use a semi classical dielectric formulation for the photoelectron trajectory, and we estimated the parameter rs, the radius of the sphere occupied by one electron in the solid, which is critical in order to define the electron density of the alloy. With the cited formulation, we have obtained a detailed behavior of the different contributions of the collective excitations in both processes.